Awe in Advertising: The Mediating Role of an Abstract Mindset. Issue 1 (1st January 2023) - Septianto, Felix; Seo, Yuri; Li, Loic Pengtao; Shi, Linsong
Abstract: Awe represents a powerful positive emotion that has received limited examination in the advertising context. The present research draws on construal-level theory to shed light on when and how awe increases persuasion. Across five experimental studies, we show that the effect of awe elicits an abstract mindset and, therefore, increases advertising persuasiveness when the advertised product emphasizes desirability features and is perceived as temporally distant. The findings offer insights about how awe influences advertising effectiveness that was heretofore lacking. Theoretical contributions and practical implications for leveraging emotional appeals in advertising are discussed.